2020
DOI: 10.1177/1756284820939453
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in inflammatory bowel disease patients treated for pneumonia

Abstract: Background: Community-acquired pneumonia is among the most common infections affecting ulcerative colitis and Crohn’s disease patients. Data regarding epidemiology and outcomes of pneumonia in inflammatory bowel disease patients is lacking. We aimed to identify predictors of adverse outcomes among inflammatory bowel disease patients treated for pneumonia. Methods: This was a retrospective cohort study that included adult patients admitted to Sheba Medical Center for pneumonia between 2012 and 2018. Data was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Burisch et al [ 33 ] described a higher rate of all-cause hospitalization among IBD patients, particularly in the early years from diagnosis. Additionally, in a previous study by our group about IBD patients treated for pneumonia, we found a higher rate of hospitalization, though no difference in adverse outcomes was observed [ 34 ]. This study indicates that patients with IBD who had had a history of recent hospitalization for any reason prior to a UTI episode had an increased risk of hospitalization and 30-day recurrent hospitalization for any reason.…”
Section: Discussionmentioning
confidence: 56%
“…Burisch et al [ 33 ] described a higher rate of all-cause hospitalization among IBD patients, particularly in the early years from diagnosis. Additionally, in a previous study by our group about IBD patients treated for pneumonia, we found a higher rate of hospitalization, though no difference in adverse outcomes was observed [ 34 ]. This study indicates that patients with IBD who had had a history of recent hospitalization for any reason prior to a UTI episode had an increased risk of hospitalization and 30-day recurrent hospitalization for any reason.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, the disease burden of IBD may increase in the presence of bronchiectasis. Supporting this notion, a recent study showed that the presence of bronchiectasis is associated with an increased risk of mortality in individuals with IBD who developed pneumonia [ 16 ]. We have provided further robust evidence that bronchiectasis is associated with poor treatment outcomes regarding mortality and healthcare use.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid bronchiectasis is believed to exacerbate the disease burden in individuals with IBD. The information on this issue is limited, with only one study indicating that the pneumonia-related mortality rate is higher in individuals with IBD and bronchiectasis than in those without bronchiectasis [ 16 ]. Consequently, whether bronchiectasis results in worse treatment outcomes in individuals with IBD remains unknown.…”
Section: Introductionmentioning
confidence: 99%